Design and implementation of an L1 adaptive proportional output feedback controller - Bagati, Deepanshu; Souanef, Toufik; Whidborne, James F. (MDPI, 2024)
A new approach for output feedback ℒ1 adaptive control based on a proportional adaptation law is presented. The effectiveness of this design is assessed in simulation and validated through real-time testing on an airfoil pitch control wind tunnel experimental rig. Experimental evaluation of the robustness of the controllers, assessed by introducing various disturbances into the control signals, shows that the adaptive control has a better performance compared to PID control, particularly in scenarios with reduced control effectiveness and time-varying disturbances. The experimental results demonstrate the efficacy of the proposed method in practical applications.
Keywords: L1 adaptive control; fault-tolerant control; output feedback control; real-time systems